Synthesis, thermal and spectroscopic study of light lanthanide nicotinate, in the solid state - Denck Colman, Tiago Andre [UNESP]; Coura Gomes, Danilo Jose [UNESP]; Caires, Flavio Junior [UNESP]; Treu Filho, Osvaldo [UNESP]; Silva, Rita de Cassia da [UNESP]; Ionashiro, Massao [UNESP] (Elsevier B.V., 2014)
Characterization, thermal stability and thermal decomposition of light trivalent lanthanide nicotinates, Ln(C6H4NO2)(3)center dot nH(2)O (Ln = La to Gd, except Pm) were synthesized and investigated employing simultaneous thermogravimetry and differential scanning calorimetry (TG-DSC), Fourier transform infrared spectroscopy (FTIR), X-ray diffractometry, complexometry and TG-DSC coupled to FTIR. In all the compounds the dehydration occurs in two consecutive steps and the thermal decomposition of the anhydrous compounds occurs in single, two, three or four consecutive steps, with the formation of the respective oxides CeO2, Pr6O11 and Ln(2)O(3) (Ln = La, Nd, Sm, Eu, Gd), as final residue. The results also provided information about the composition, thermal behavior, identification of gaseous products evolved during the thermal decomposition of these compounds. Furthermore, the theoretical and experimental spectroscopic data suggest the possible modes of coordination of the ligand with the metals. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Lanthanides; Nicotinates; Thermal behavior; Evolved gases; DFT